Personal Pronouns in Balinese and English With Reference To Tiga Satua Bali - I Gusti Ayu Agung Sintha Satwika; Ketut Artawa; Ni Luh Ketut Mas Indrawati (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2016)
This research is aimed at investigating and analyzing the meaning and application of personal pronouns in Balinese and English. The data of this writing were collected from a bilingual book entitled Tiga Satua Bali. This study was conducted using the qualitative method of which the discussion was presented descriptively. The data of this study were collected using observation technique and were analyzed using the qualitative method and comparative technique. The result of this study indicates that the personal pronouns can be classified into three, namely first, second, and third personal pronouns which  can be found in Basa Singgih, Andap, and Kasar. This classification was made based on the context of situation and speech participants